Melanopic Contribution of Display Image to Alertness, Attention, Brightness Perception, and Visual Fatigue - Nianfang Zhu; Yan Tu; Lili Wang; Yunyang Shi (IEEE Photonics Journal, 2025)
The melanopic contribution to visual and non-visual effects has garnered growing concern, particularly in lighting research. However, its impacts caused by display images remain understudied. This research investigated the influence of melanopic luminance of display images on visual effects like brightness perception and visual fatigue, as well as non-visual effects such as alertness and attention based on a 65-inch four-primary display system. A 300 lx photopic environment was adopted to ensure rod saturation. The metameric images were modulated at two melanopic luminance levels (higher and lower). A multimodal assessment, including subjective brightness ratings, Karolinska Sleepiness Scale (KSS) evaluations, reaction time of Psychomotor Vigilance Task (PVT), d2 test of attention performance metrics, eye movement parameters, and visual function parameters was applied. The results showed that images with higher melanopic luminance level elicited longer fixation duration as well as fewer blinks and fixations, indicating improved attention. It was also supported by better d2 test performance at higher melanopic luminance level. Further, the difference in eye movement parameters between the two melanopic luminance levels showed that not only the Michelson contrast of the melanopic luminance levels, but also the melanopic luminance value itself played an important role. Moreover, a smaller increase in reaction time at higher melanopic luminance level implied heightened alertness, whereas the greater reduction in accommodation and convergence parameters indicated more pronounced visual fatigue. Subjective evaluation revealed that images with higher melanopic luminance level appeared brighter, supported by smaller pupil area.